Female leadership and gender equity: Evidence from plant closure - Tate, Geoffrey; Yang, Liu (Journal of Financial Economics, 2015)
We use unique worker-plant matched panel data to measure differences in wage changes experienced by workers displaced from closing plants. We observe larger losses among women than men, comparing workers who move from the same closing plant to the same new firm. However, we find a significantly smaller gap in hiring firms with female leadership. The results are strongest among women who are displaced from male-led plants and from less competitive industries. Our results suggest an important externality to having women in leadership positions: They cultivate more female-friendly cultures inside their firms.